Long-term impact of the SARS-CoV-2 pandemic on respiratory viruses in Germany - Eggeling, Ralf; König, Florian; Köppel, Lisa; Böhler, Laura-Inés; Böhm, Michael; Schmeißer, Norbert; Pfeifer, Nico; Kaiser, Rolf; Schnitzler, Paul (BMC public health, 2025)
Respiratory viral diseases are one of the greatest challenges facing our healthcare system, with them being one of the main causes of death. This has been demonstrated once again by the impact of the SARS-CoV-2 pandemic in recent years. We study the impact of the SARS-CoV-2 pandemic on the prevalence of respiratory viruses by analysing a subset of the Clinical Virology network database, covering 2,216,198 samples tested for 18 different viral pathogens in the time span from 2010 to 2024.
The Clinical virology network: Albert Heim, PhD, Andi Krumbholz, MD, Andreas Lindauer, PhD, Andreas Sauerbrei, MD, Andres Anton Pagarolas, PhD, Anna-Maria Eis-Hübinger, PhD, Annemarie Berger, Dr. med. vet., Annette Devide, MD, Astrid Kehlen, PhD, Albrecht Oehme, MD, Babett Wintsche, PhD, Barbara C. Gärtner, MD, Barbara Schmidt, MD, Benedikt Weissbrich, PhD, Bert Niesters, PhD, Carsten Bartling, PhD, Carsten Tiemann, PhD, Christian Aepinus, PhD, Christian G. Schüttler, MD, Daniela Huzly, MD, Detlef Michel, PhD, Dieter Hoffmann, MD, Elisabeth Puchhammer-Stoeckl, PhD, Theresa Popow Kaup, PhD, Monika Redlberger, PhD, Hajo Grundmann, MD, Hans Nitschko, PhD, Hans-Joachim Siemens, MD, Harald Kessler,MD, Jan Philipp Jung, PhD, Jens Dreier, PhD], Joachim Kühn, MD, Jörg Hofmann, Katrin Palupsky, Kerstin Weise, PhD, Marcena Griego, Martin Obermeier, MD, Meri Gorgievski, MD, Michael Kleines, PhD, Patricia Bartsch, Paul Schnitzler, PhD, Peter Gohl, PhD, Phillipp Kirfel, PhD, Robert Beck, MD, Rolf Kaiser, PhD, Sandra Hauka, MD, Thomas Meyer, PhD, Thomas Ziegler, PhD, Uwe Gerd Liebert, PhD, Walter Bossart, PhD, Wegene Borena, PhD, Wolfgang Gulich
Gesehen am 04.12.2025